Dampak Kebijakan Cukai Rokok terhadap Distribusi Surplus Ekonomi Industri Rokok di Indonesia - Antik Suprihanti; nFN Harianto; Bonar Marulitua Sinaga; Reni Kustiari (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2019)
EnglishIndonesian government has applied cigarette excise tax policy on clove cigarette which impacts on the rise of cigarette price and cigarette production. Because of tobacco and clove demand are derived demand of cigarette supply, so the change on cigarette production impacts on demand of cigarettes input (tobacco and clove) and it eventually impact on the price of these commodities. The rise of cigarette excise not only impacts on economic surplus of producer and consumer of cigarettes, but also on tobacco and clove farmers. Clove cigarette encompasses hand-rolled clove cigarettes (SKT), machine-rolled clove cigarettes (SKM) and klobot cigarettes (SKB). The aim of this research was to analyze the impact of the rise of cigarette excise tax policy toward economic surplus distribution among the economic agents on Indonesian cigarette industries. This research accomodated the data series of 1990-2016 with simultaneous equation system which consisting of 36 structural equations and 25 identity equations. This model was estimated by using 2 SLS (Two-Staged Least Squares) method. The results showed that cigarette excise tax impacted on the rise of government revenue and total economic surplus negatively. The rise of excise tax impacted on negative surplus of cigarette producer decreased, negative surplus of cigarette consumer increased, and farmer surplus decreased (negative). In order to keep positive economic surplus of the farmer, the rise of SKT cigarette tax maximum should be constituted no more than 5,8%. To anticipate the loss of farmer surplus and the decrease of tobacco and clove demand ini the future, the government can use the tax revenue to develop alternative crops besides tobacco such as vegetables, intensification of tobacco as import subtitution and develop diversification of clove products for essential oil, preservatives and others.IndonesianPemerintah Indonesia telah menerapkan kenaikan tarif cukai rokok kretek yang berdampak pada kenaikan harga rokok dan produksi rokok. Oleh karena permintaan tembakau dan cengkeh merupakan permintaan turunan dari penawaran rokok, maka perubahan produksi rokok akan berdampak pada permintaan input (tembakau dan cengkeh) dan berdampak pada harga kedua komoditas tersebut. Kenaikan cukai tidak hanya berdampak pada surplus ekonomi produsen dan konsumen rokok, tetapi juga petani tembakau dan cengkeh. Industri sigaret kretek meliputi sigaret kretek tangan (SKT), sigaret kretek mesin (SKM) dan rokok klobot (SKB). Tujuan penelitian ini adalah untuk menganalisis dampak kenaikan cukai rokok terhadap distribusi surplus ekonomi di antara pelaku ekonomi pada industri rokok di Indonesia. Penelitian ini menggunakan data deret waktu tahun 1990-2016 dengan sistem persamaan simultan yang terdiri dari 36 persamaan struktural dan 25 persamaan identitas, yang diestimasi menggunakan metode 2SLS (Two-Staged Least Squares). Hasil penelitian menunjukkan adanya tarif cukai rokok akan menambah penerimaan pemerintah namun berdampak negatif terhadap total surplus ekonomi. Kenaikan cukai rokok berdampak pada negatif surplus produsen rokok makin menurun, negatif surplus konsumen rokok makin meningkat dan surplus petani menjadi turun (negatif). Agar surplus ekonomi petani tetap positif, maka kenaikan tarif cukai khususnya SKT ditetapkan tidak lebih dari 5,8%. Pemerintah dapat memanfaatkan sebagian penerimaan cukai rokok untuk melakukan upaya pengembangkan alternatif tanaman lain selain tembakau seperti sayuran, intensifikasi tanaman tembakau subtitusi impor dan melakukan diversifikasi produk cengkeh sebagai minyak esensial, pengawet dan lainnya untuk mengatasi kerugian petani dan mengantisipasi turunnya permintaan tembakau dan cengkeh pada masa depan.